Vapor Inhalation Therapy (Eucalyptus) Introduction to The Event of ARI in Toddlers - Dewi Kurniati; Siti Satikah; Bunga Tiara Carolin (Nursing and Health Sciences Journal (NHSJ), 2022)
ARI is an upper respiratory tract infection, based on data from April-July, researchers obtained data on 175 patients with ARI. 92 ARI in toddlers and 44 in children and 39 in adults. With an average experience of ARI with moderate signs and symptoms. Common symptoms are usually fever, shortness of breath, severe cough producing a large amount of mucus, high fever steam inhalation therapy is an effective treatment for nasal congestion. Clogged, good natural method whit steam and heat. This study to determine the Effect of Eucalyptus (Eucalyptus) Oil Steam Inhalation Therapy on the Incidence of ARI in Toddlers at the Cikedal Public Health Center, Pandeglang Regency, Banten Province in 2021. The method in this research is Quasi Experimental Design. The research design used was a two group pre-post test and control design. The sample in the study was 30 respondents, consisting of 15 respondents from the experimental group and 15 respondents from the control group. Data were analyzed using Paired T-test and Independent T-test. The Results: the average score of incidence of ARI pretest in the experimental pretest group was 5.33 while the posttest was 2.87 and the average difference was 2.6, the average score for the incidence of ARI pretest in the control group was 5.40 while the posttest was 5.20 and the average difference of 0.2 Independent T-test results obtained p-value 0.000 the conclusions and suggestions, there was an effect of eucalyptus (eucalyptus) vapor inhalation therapy on the incidence of ARI among toddlers at the Cikedal Public Health Center, Pandeglang Regency, Banten Province. It is hoped that health workers will implement the application of eucalyptus oil inhalation therapy to reduce ARI in toddlers.